MORPHOLOGICAL AND PHYSIOLOGICAL CHARACTERS OF CASSAVA (MANIHOT ESCULENTA CRANTZ) WHICH WET TOLERANT - Rahmawati Rahmawati; Tri Agus Siswoyo; Didik Puji Restanto; Sri Hartatik; Sigit Soeparjono; Sholeh Avivi (UNEJ e-Proceeding, 2016)
Weather conditions often unstable changed and increase the floods of agricultural land. Land which was originally drought will experience wetness and need variety of a plant that wetness tolerant. This study were aimed to get cassava that wet tolerant and to study the morphological, physiological characters of cassava grown on wetness land. The experiment was conducted based on factorial random plot design that consisting two factors with five replications. The first factor were four varieties namely: V1 = Daun Ganja; V2 = Sawi Ketan; V3 = Kasesat Beracun; V4 = Gajah. The second factor was wet treatment consisting of 2 the condition that were K0 = as control, media with 100% field capacity; K1 = as wet treatment by watering of media maintain on -10 cm from media surface. The difference between treatments tested with Duncan Multiple Range Test (DMRT) with the probability 5%. Wet treatment started when plant aged was 2 months after planting, during eight weeks. The observations on variables based on morphological and physiological characters. Result showed that every varieties give the different response on wet treatment. Best response on wet tolerant variety shown by variety code of V2 (Sawi Ketan) were indicated by plant height, total leaf number produced, stem diameter, fresh weight of root, dry weight of root, fresh weight of shoot, dry weight of shoot, photosynthesis index, stomata conductivity and root volume.